The Role of Nuclear Energy in Uzbekistan - Xolixmatov Baxriddin Berdi ugli (Zien Journals, 2022)
This article describes the ongoing reforms in the field of nuclear energy in Uzbekistan. In addition, the problems and prospects of nuclear energy, the main problems that may arise in the field are highlighted.
Keywords: energy; nuclear power; thermal pollution; reforms